Challenges in Diagnosis and Treatment of a Cervical Spinal Cord Injury Patient with Melanoma, Adenocarcinoma, and Hepatic and Osteolytic Metastases: Need to Implement Strategies for Prevention and Early Detection of Cancer in Spinal Cord Injury Patients. (20th November 2012) - Vaidyanathan, Subramanian; Mansour, Paul; Hughes, Peter L.; Selmi, Fahed; Singh, Gurpreet; Pulya, Kamesh; Soni, Bakul M.
Abstract : A male tetraplegic patient with, who had been taking warfarin, developed haematuria. Ultrasound scan revealed no masses, stones, or hydronephrosis. Urinary bladder had normal configuration with no evidence of masses or organised haematoma. Urine cytology revealed no malignant cells. Four months later, CT urography revealed an irregular mass at the base of urinary bladder. Cystoscopic biopsy revealed moderately differentiated adenocarcinoma, which contained goblet cells and pools of mucin showing strongly positive immunostaining for prostatic acid hosphatase and patchy staining for prostate specific antigen. Computed Tomography revealed multiple hypodense hepatic lesions and several osteolytic areas in femoral heads and iliac bone. With a presumptive diagnosis of prostatic carcinoma, leuprorelin acetate 3.75 mg was prescribed. This patient expired a month later. Conclusion . (i) Spinal cord injury patient, who passed blood in urine while taking warfarin, requires repeated investigations to look for urinary tract neoplasm. (ii) Anti-androgen therapy should be prescribed for 2 weeks prior to administration of gonadorelin analogue to prevent tumour flare causing bone pain, bladder outlet obstruction, uraemia, and cardiovascular risk due to hypercoagulability associated with a rapid increase in tumour burden. (iii) Spinal cord physicians should adopt a caring and compassionate approach while managing tetraplegic patients with several co-morbidities, as aggressive diagnostic tests and therapeutic procedures may lead to deterioration in the quality of life.